Short-Term Repeated Wingate Training in Hypoxia and Normoxia in Sprinters - Takei, Naoya; Kakinoki, Katsuyuki; Girard, Olivier; Hatta, Hideo (Frontiers in Sports and Active Living, 2020)
Repeated Wingate efforts (RW) represent an effective training strategy for improving exercise capacity. Living low-training high altitude/hypoxic training methods, that upregulate muscle adaptations, are increasingly popular. However, the benefits of RW training in hypoxia compared to normoxia on performance and accompanying physiological adaptations remain largely undetermined. Our intention was to test the hypothesis that RW training in hypoxia provides additional performance benefits and more favorable physiological responses than equivalent training in normoxia. Twelve male runners (university sprinters) completed six RW training sessions (3 × 30-s Wingate “all-out” efforts with 4.5-min recovery) in either hypoxia (FiO2: 0.145, n = 6) or normoxia (FiO2: 0.209, n = 6) over 2 weeks. Before and after the intervention, participants underwent a RW performance test (3 × 30-s Wingate “all-out” efforts with 4.5-min recovery). Peak power output, mean power output, and total work for the three exercise bouts were determined. A capillary blood sample was taken for analyzing blood lactate concentration (BLa) 3 min after each of the three efforts. Peak power output (+11.3 ± 23.0%, p = 0.001), mean power output (+6.6 ± 6.8%, p = 0.001) and total work (+6.3 ± 5.4% p = 0.016) significantly increased from pre- to post-training, independently of condition. The time × group × interval interaction was significant (p = 0.05) for BLa. Compared to Pre-tests, BLa values during post-test were higher (+8.7 ± 10.3%) after bout 2 in the normoxic group, although statistical significance was not reached (p = 0.08). Contrastingly, BLa values were lower (albeit not significantly) during post- compared to pre-tests after bout 2 (-9.3 ± 8.6%; p = 0.08) and bout 3 (-9.1 ± 10.7%; p = 0.09) in the hypoxic group. In conclusion, six RW training sessions over 2 weeks significantly improved RW performance, while training in hypoxia had no additional benefit over normoxia. However, accompanying BLa responses tended to be lower in the hypoxic group, while an opposite pattern was observed in the normoxic group. This indicates that different glycolytic and/or oxidative pathway adaptations were probably at play.